SISTEM ANALISIS DATA MAHASISWA MENGGUNAKAN APLIKASI ONLINE ANALYTICAL PROCESSING (OLAP) DATA WAREHOUSE - Supriyatna, Adi (LPPM Universitas Nusa Mandiri, 2016)
Along with the developments of the times and technology then the education level of community has been an increase in , this is proven by the increasing interest on the part of high school graduates who want to continue the level of education to college. The development of a collegecan be seen at the rising numbers of students from year to year. At this point in time leaders the top of college difficulty receive information related to the number of student who in conformity with the wish because they still relying on parts that perform data processing student , as a result have to wait to get the information relating to data student. In addition, dataset students such abounding actually has information or knowledge can get or analyze, so as to from a collection of the data can be obtained a pattern or knowledge that can be used by a college to better understand the condition there are. Based on the knowledge obtained from data analysis students , leaders universities can make strategic plan better to embodied in the work program forward. This research was intended to produce a system that can be used by the leader of universities to an analysis of data students to design application olap data the warehouse. The method or approach that is used in the design this system is the approach top down. The result of this research is the establishment of application OLAP data warehouse to enable to the college in do the digging information on and analysis of students data so that it can be speed up the decision-making process, and can provide independence in choosing a form of report desired.